(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Metformin's effects on vitamin B12 decrease have been the subject of mixed findings from randomised controlled trials and observational research. Therefore, we conducted a comprehensive review to investigate whether or not metformin affects serum levels of vitamin B12.